AMS‐800 Artificial urinary sphincter in female patients with stress urinary incontinence: A systematic review. (9th October 2018) - Peyronnet, Benoit; O'Connor, Eabhann; Khavari, Rose; Capon, Grégoire; Manunta, Andrea; Allue, Marta; Hascoet, Juliette; Nitti, Victor W.; Gamé, Xavier; Gilleran, Jason; Castro‐Sader, Luis; Cornu, Jean‐Nicolas; et al.
Abstract : Aims: To perform a systematic review of studies reporting the outcomes of AMS‐800 artificial urinary sphincter (AUS) implantation in female patients with stress urinary incontinence (SUI) resulting from intrinsic sphincter deficiency (ISD). Methods: A systematic literature search of the Medline and Embase databases was performed in June 2018 in accordance with the PRISMA statement. No time limit was used. The protocol was registered in PROSPERO (CRD42018099612). Study selection and data extraction were performed by two independent reviewers. Results: Of 886 records screened, 17 were included. All were retrospective or prospective non‐comparative case series. One study reported on vaginal AUS implantation, 11 on open AUS implantation, two on laparoscopic AUS implantation, two on robot‐assisted AUS implantation and one compared open and robot‐assisted implantations. The vast majority of patients had undergone at least one anti‐incontinence surgical procedure prior to AUS implantation (69.1‐100%). The intraoperative bladder neck injury rates ranged from 0% to 43.8% and the intraoperative vaginal injury rates ranged from 0 to 25%. After mean follow‐up periods ranging from 5 to 204 months, the complete continence rates ranged from 61.1% to 100%. The rates of explantation, erosion and mechanical failure varied from 0% to 45.3%, 0% to 22.2% and 0% to 44.1%, respectively. Conclusions: AMS‐800 AUS can provide excellent functional outcomes in female patients with SUI resulting from ISD but at the cost of a relatively high morbidity. High level of evidence studies are needed to help better define the role of AUS in the female SUI armamentarium.